Analisis Persepsi dan Sikap Anggota terhadap Produk Pembiayaan Koperasi Konsumen Syari’ah Pegawai RSUD Dr Achmad Mochtar Bukittinggi - Ayunda Murni Andini; Aidil Alfin (ARZUSIN, 2026)
The development of Islamic cooperatives in Indonesia has shown significant growth as an alternative financial institution operating based on Islamic principles. However, studies that specifically discuss members’ perceptions and attitudes toward financing products in cooperatives that have transformed from a conventional system to an Islamic system remain relatively limited. This study aims to analyze members’ perceptions and attitudes toward the financing products of Koperasi Konsumen Syariah Pegawai RSUD Dr. Achmad Mochtar Bukittinggi, which include murabahah financing, ijarah multijasa, and non-cash gold sale and purchase. This study uses a qualitative approach with a field research design and a qualitative descriptive method. Informants were selected through purposive sampling, consisting of cooperative administrators and members who use Islamic financing products. Data were collected through semi-structured interviews, observation, and documentation, and were then analyzed using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing and verification. The results show that members’ perceptions of Islamic financing products were in the positive category, shaped by the transparency of contract information, conformity with Islamic principles, economic benefits, religiosity factors, and loyalty to the cooperative. Members’ attitudes also showed a supportive tendency, indicated by comfort in using the Islamic financing system, willingness to recommend the products to other members, acceptance of financing margins, and commitment to continue using the cooperative’s products. The conclusion of this study affirms that members’ positive perceptions and attitudes are important factors in the acceptance of Islamic financing products in cooperatives undergoing institutional transformation. The implications of this study indicate the need to strengthen Islamic financial education, transparency of contract information, and service quality improvement so that Islamic cooperatives can expand members’ trust and loyalty.